Effect of kinesiology tape application direction on quadriceps strength. Issue 24 (June 2018) - Choi, Im-Rak; Lee, Jung-Hoon
Abstract: Background: Controversy exists regarding whether the kinesiology tape application direction affects muscle strength. Methods: Eighteen healthy volunteers (12 men, 6 women) participated. Kinesiology tape was randomly applied to the quadriceps muscles either from origin to insertion or from insertion to origin. A Biodex isokinetic dynamometer was used to measure the peak torque of the quadriceps pre-and post-taping. Results: There was a significant difference in muscle strength after taping, regardless of the kinesiology tape application direction. There were no significant differences in the peak torque of the quadriceps between the 2 kinesiology tape application directions. Conclusions: The application of kinesiology tape application to the rectus femoris, vastus medialis, and vastus lateralis of the quadriceps increased the muscle torque, regardless of the tape application direction. Therefore, to enhance quadriceps strength, we recommend the application of kinesiology tape to 3 of the muscles of the quadriceps (specifically, the rectus femoris, vastus medialis and vastus lateralis), irrespective of the tape application direction.